Interval between first dose and booster affected antibody production in cattle vaccinated against rabies - Albas, Avelino [UNESP]; Fontolan, O. L. [UNESP]; Pardo, P. E.; Bremer Neto, H.; Sartori, Alexandrina [UNESP] (FapUNIFESP (SciELO), 2006)
In this study, we compared the levels of neutralizing antibodies induced by inactivated rabies vaccine in cattle by using three alternative immunization procedures. Forty-five bovines (breed nelore) were then organized in three groups (A, B and C, with 15 animals/group). Group A received only one vaccine dose at day zero and Group B received the first dose at day zero and then another dose at day 30 (early booster). Group C was also immunized with two doses; however, the booster was postponed until day 180 after the first dose (delayed booster). Blood samples were withdrawn at days zero (before the first dose) and 30, 210, 390, and 540 after the beginning of immunization and the antibody titers were evaluated by mouse neutralization test. The protocol used to immunize Group C (booster at day 180) was clearly more efficient. In this group, antibody levels were higher and also remained higher for longer periods in comparison with the other two groups. These results show that booster timing significantly affected antibody levels. Therefore, programs addressed to control this disease in cattle should consider not only the use of a booster but also its administration time.
Keywords: Antibody; Cattle; Neutralization; Rabies; Vaccine; Bos taurus